1998
DOI: 10.1152/jappl.1998.84.4.1475
|View full text |Cite
|
Sign up to set email alerts
|

Body composition by air-displacement plethysmography by using predicted and measured thoracic gas volumes

Abstract: The BOD POD, a new air-displacement plethysmograph for measuring human body composition, utilizes the inverse relationship between pressure and volume (Boyle's law) to measure body volume directly. The quantity of air in the lungs during tidal breathing, the average thoracic gas volume (Vtg), is also measured by the BOD POD by using a standard plethysmographic technique. Alternatively, the BOD POD provides the use of a predicted Vtg (Vtgpred). The validity of using Vtgpred in place of measured Vtg (Vtgmeas) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
2
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(119 citation statements)
references
References 16 publications
10
97
2
2
Order By: Relevance
“…A detailed description of the procedure is given in earlier reports (Dempster & Aitkens, 1995;McCrory et al, 1995). Since McCrory et al found no signi®cant difference between measured and predicted V TG in adults (McCrory et al, 1998), a predicted estimate of V TG based on age, sex, and height was used in cases where an accurate measurement of V TG was not possible. The between-day CV for B d estimates by ADP in our laboratory was determined in four adult subjects measured on four consecutive days.…”
Section: Body Composition Measurementsmentioning
confidence: 99%
“…A detailed description of the procedure is given in earlier reports (Dempster & Aitkens, 1995;McCrory et al, 1995). Since McCrory et al found no signi®cant difference between measured and predicted V TG in adults (McCrory et al, 1998), a predicted estimate of V TG based on age, sex, and height was used in cases where an accurate measurement of V TG was not possible. The between-day CV for B d estimates by ADP in our laboratory was determined in four adult subjects measured on four consecutive days.…”
Section: Body Composition Measurementsmentioning
confidence: 99%
“…Caucasian women, aged 63 Ϯ 2 years (range 55-79), with a BMI of 29.9 Ϯ 0.7 kg/m 2 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and who were not actively involved in any physical training, volunteered to participate in this 7-week outpatient study. The women were recruited from the Little Rock, Arkansas, region via advertisements in local newspapers.…”
Section: Subjects a Total Of 22 Postmenopausalmentioning
confidence: 99%
“…Body density was determined via airdisplacement plethysmography using BOD POD (Life Measurements Instruments, Concord, CA) (30). Percent body fat (BF), FM, and fat-free mass (FFM) were estimated from body density using the Siri two-compartment model equation (31).…”
Section: Subjects a Total Of 22 Postmenopausalmentioning
confidence: 99%
“…Alternatively, the BOD POD provides the use of a predicted V TG (V TGPredicted ) (Crapo et al, 1982). The validity of using the V TGPredicted in place of the measured V TG (V TGMeasured ) to determine %FM was studied in a few cross-sectional studies with mixed results (McCrory et al, 1998;Demerath et al, 2002). Accordingly, no differences were found between measured vs predicted V TG in different adult age groups.…”
Section: Introductionmentioning
confidence: 99%